Malaria programme personnel's experiences, perceived barriers and facilitators to implementing malaria elimination strategy in South Africa - Hlongwana, KW; Sartorius, B; Tsoka-Gwegweni, J (BioMed Central, 2018)
BACKGROUND: South Africa has set an ambitious goal targeting to eliminate malaria by 2018, which is consistent with the United Nations Sustainable Development Goals' call to end the epidemic of malaria by 2030 across the globe. There are conflicting views regarding the feasibility of malaria elimination, and furthermore studies investigating malaria programme personnel's perspectives on strategy implementation are lacking. METHODS: The study was a cross-sectional survey conducted in 2014 through a face-to-face investigator-administered semi-structured questionnaire to all eligible and consenting malaria programme personnel (team leader to senior manager levels) in three malaria endemic provinces (KwaZulu-Natal, Mpumalanga, and Limpopo) of South Africa. RESULTS: The overall response rate was 88.6% (148/167) among all eligible malaria personnel. The mean age of participants was 47 years (SD 9.7, range 27-70), and the mean work experience of 19.4 years (SD 11.1, range 0-42). The majority were male (78.4%), and 66.9% had secondary level education. Awareness of the malaria elimination policy was high (99.3%), but 89% contended that they were never consulted when the policy was formulated and few had either seen (29.9%) or read (23%) the policy, either in full or in part. Having read the policy was positively associated with professional job designations (managers, EHPs and entomologists) (p = 0.010) and tertiary level education (p = 0.042). There was a sentiment that the policy was neither sufficiently disseminated to all key healthcare workers (76.4%) nor properly adapted (68.9%) for the local operational context in the elimination strategy. Most (89.1%) participants were not optimistic about eliminating malaria by 2018, as they viewed the elimination strategy in South Africa as too theoretical with unrealistic targets. Other identified barriers included inadequate resources (53.5%) and high cross-border movements (19.8%). CONCLUSIONS: Most participants were not positive that South Africa could achieve the malaria elimination goal by 2018, citing the high cross-border movements and lack of resources as key barriers. The National and relevant Provincial Departments of Health should consider investing more time and resources in further stakeholder engagement for more effective implementation of malaria elimination strategy in South Africa.